Novel Immune-Related Genetic Expression for Primary Sjögren's Syndrome - Cui, Jiajia; Li, Hui; Wang, Tianling; Shen, Qin; Yang, Yuanhao; Yu, Xiujuan; Hu, Huaixia (Frontiers in Medicine, 2022)
Objective: To identify novel immune-related genetic expression for primary Sjogren’s syndrome (pSS). Methods: Gene expression profiles were obtained from the Gene Expression Omnibus database, and differentially expressed genes (DEGs) were screened. The differences in immune cell proportion between normal and diseased tissues were compared, and weighted gene co-expression network analysis was conducted to identify the key module. The key genes were then obtained, followed by a protein–protein interaction (PPI) network and enrichment analysis. Then, the feature genes were screened and verified using the GEO datasets and Quantitative real-time PCR (qRT-PCR). Results: A total of 345 DEGs were identified, and the proportions of delta gamma T cells, memory B cells, regulatory T cells (Tregs), and activated dendritic cells in normal and pSS groups were significant difference. The turquoise module had the highest correlation with pSS, and 252 key genes were identified. The PPI network of key genes showed that RPL9, RBX1, and RPL31 had a higher degree. In addition, the key genes were mainly enriched in coronavirus disease-COVID-19, hepatitis C, and influenza A. Fourteen feature genes were obtained using the support vector machine model, and two subtypes were identified. The genes in the two subtypes were mainly enriched in the JAK-STAT, P53, and Toll-like receptor signaling pathways. Almost all the feature genes up-regulated in pSS group were verified in the GEO datasets and qRT-PCR. Conclusion: Memory B cells, delta gamma T cells, Tregs, activated dendritic cells, RPL9, RBX1, RPL31, and these feature genes might paly vital roles in the development of pSS.